Theory and Practice of Interventionist State Building: Paradoxes and Limitations - Shahida Aman; Shagufta Aman (Journal of Political Studies, 2014)
The end of Cold War period significantly increased the frequency of civil war occurrences; resulting humanitarian and security challenges prompted the UN and international community to embark on a pro-active interventionist peace building and state building role in conflict states. Interventionist state building has developed as a major concern for the international state system in the last two decades. This paper argues that interventionist state building theory and practice is an extension of the contemporary state failure discourse. Since failed states are measured against Weberian criteria of stateness, state building is theorized as building of effective and capable formal state institutions and practiced as introduction of depoliticized, technical centralized institutions, including the security forces, a bureaucracy and judicial structures. It further stresses that the institutional model of state building when imposed in failed and conflict settings generates a set of paradoxes and dilemmas which complicates the attainment of state building goals. The findings of the paper suggest that paradoxes are generated because institution building aims at creating effective institutions, but its foreign control and component discourages local and indigenous ownership of the state building process and creates a culture of dependency. Institutional effectiveness is also restricted by coordination dilemmas resulting from involvement of multiple external actors in the restructuring of state institutions. Low resource commitments for institutional reforms and lack of accountability to the local populace by international transitional administrations create new sets of paradoxes. All this is further complicated by resource diversion to NGOs and failures to decentralize administrative and revenue practices. These issues are discussed in the light of contemporary evidence from postintervention state building practice in the Balkans (Bosnia and Kosovo), Cambodia, East Timor and Iraq.